ISOLASI, KARAKTERISASI DAN UJI ANTAGONIS BAKTERI SELULOLITIK TERHADAP Phytophthora capsici ASAL TANAMAN LADA (Piper nigrum L.) SECARA IN-VITRO - Khaeruni, Andi; Satrah, Vit Nehru; Mariadi, Mariadi (Jurnal Agroteknos, 2011)
ABSTRACT The Aim of this experiment was obtain cellulolitic bacteria that has antagonistic potential toward P. capsici of pepper isolated under in-vitro test. The experiment was begun in isolation and selection of cellulolitic bacteria from soil samples were taken from some location at Southeast Sulawesi. Selected 20 isolates of cellulolitic bacteria examined for its morphological and physiological characteristics as well as antagonistic potential toward P. capsici of pepper isolated under in-vitro test on Potato Dextrose Agar (PDA) medium. The potential antagonistic test was carry out used randomized complete design with three replications to observes the ability of cellulolitic bacteria inhibited mycelium growth of P. capsici on PDA medium. Results showed the selected isolates very divers on morphological characters in size, pigmentation, shape, and elevation of surface. Physiological character showed that out of 20 isolates, 12 isolates have negative Gram reaction and 8 isolates positive Gram reaction. Obtaining 5 isolates very strongly, 11 isolates strongly and 4 isolates weak activities on secreted extracellular cellulose enzyme, all of isolates were facultative anaerobe activity. Further test on antagonistic ability showed that STS15c and STS12c2 isolates are the best isolates to inhibited mycelium growth of P. capsici on PDA medium in potential inhibited were 53.16% and 52.02% respectively. Key words: Cellulolitic bacteria, Phytophthora capsici, antagonistic